Effect of IMF Structural Adjustment Programs on Expectations : The Case of Transition Economies - Imam, Patrick (IMF Working Papers; Working Paper ;, 2007)
We analyze the effect of IMF programs on economic agents' expectations about the economy in transitional countries using survey data from the Central and Eastern Eurobarometer poll, an annual general public survey monitoring the evolution of public opinion from 1990 to 1997. Previous studies, in contrast, have looked at indirect measures, such as capital flows or yield spreads, to assess the impact of IMF programs on economic expectations. Using a multinomial probit model, we find that IMF loans appear to have a strong effect on agent expectations in the early years, through the inflow of real money, and through the signaling effect. IMF programs during periods of collapsing growth appear to reinforce underlying expectations for the future; they are associated with positive expectations for those with an optimistic outlook and negative expectations for those with a negative outlook. Once recovery is underway, and economic uncertainty diminishes, it appears that IMF programs cease to have a statistically significant effect on the expectations of economic agents. This suggests that IMF programs have the biggest impact on expectations during periods of great uncertainty and less of an impact when countries are subject to minor shocks.